Peran Net Interest Margin Dalam Memediasi Hubungan Faktor-Faktor Yang Mempengaruhi Return On Asset - Puji Endah Purnamasari; Intan Iriana Renanda (JPS (Jurnal Perbankan Syariah), 2022)
This research aims to show the effect of capital adequacy ratio (CAR), non-performing financing (NPF), and operating costs of operating income (OCOI) on return on assets (ROA) with net interest margin (NIM) as an intervening variable. This quantitative research uses secondary data in panel data with a purposive sampling technique. The sample used was five Islamic commercial banks (ICB) registered with the Financial Services Authority (FSA) from 2016 to 2020. Data analysis uses descriptive, stationary, regression, classical assumptions, and path analysis. This research shows that CAR, NPF, and OCOI partially do not affect NIM. CAR has a positive and significant effect on ROA. OCOI has a negative effect on ROA. NPF does not affect ROA. NIM has a positive and significant effect on ROA. NIM cannot mediate the effect of CAR on ROA. However, NIM can mediate the effect of NPF and OCOI on ROA. This research complements existing theories and can be used to reference ICB in improving performance.